Producing a popular image of the Amazon rainforest and indigenous peoples in picturebooks in English-speaking societies - Aleksandra Wierucka (Problemy Wczesnej Edukacji)
For many years the media have presented the rainforest as a fascinating and exotic place, abundant in various species of plants and animals, the home of people decorated with feathers or holding spears. Picturebooks are no exception. This article presents the ways a popular image of the Amazon forest is produced in picturebooks for young readers in English-speaking industrialised societies. The analysis shows that shaping knowledge about the tropical forest is based on stereotypes about the “untouched pristine forest” populated by “wild indigenous people” – a notion that is spurious. Some of these books undertake the subject of indigenous knowledge or the loss of cultural identity. However the presentation of these issues often lacks deeper dimensions. The exoticisation of rainforest inhabitants as well as the forest itself may have a negative impact on young readers’ understanding of the cultural diversity of the Amazon, as well as their understanding of the complexity of indigenous peoples’ lives.